A Study on Heavy Metal Soil Contamination in Cocoa Plantations in South West Region, Cameroon - Manga, Veronica Ebot; Fru, Bridget Ngeminy; Sendze, Godwin Yinda (Geography, Earth Science and Environment: Research Highlights Vol. 10, 2025)
In Cameroon, like in many other developing countries, agricultural practices rely heavily on agrochemicals to prevent and/or control the crops threatening diseases. The status of heavy metal contamination of surface soils in two cocoa plantations of approximately 30 years in Cameroon was evaluated. The study area is located to the West of the Mungo River, where significant limestone and isolated basaltic rocks are exposed, while in the north (around Ediki) isolated shaley units are exposed. Limestone and recent alluvium occur closer to the banks of the Mungo River. Two farms, referred to henceforth as Farm A and B, were included in the study. The bioavailable fractions of Fe, Cu, Zn, Cd and Cr were used to assess the extent of heavy metal contamination using a selection of contamination indices. In addition, other physicochemical properties including organic matter, particle size, CEC and pH were also assessed. One of the farms was dominated by sand (64.56% - 73.46% sand) in contrast to the other (2.56% to 37.51%) and the latter had a higher clay content. The order of abundance of heavy metals, as expressed by the mean values, is as follows Fe > Cu > Zn > Cr > Cd in soils from the two areas. The contamination Factors of Cu-, Zn- and Cd are considerable for clay-dominated soil. The potential ecological risk of the metals in both soils was low with the exception of Cd in the clayey soil. Results for hazard assessment showed Cu levels were within the low ISQC sediment criteria in the clay-dominated soil; possibly linked to the long-term application of Cu-fungicide. This suggests that Cu, Zn and Cr inputs to the soils may be attributable to anthropogenic activities, specifically agriculture. In conclusion, among the elements, Cu levels are within the low ISQC sediment criteria in soil B. Its concentration is associated with the long-term application of Cu-fungicide. Cd levels in soil B, are of high ecological risk following the Er index.